Assessment of Clinical Reasoning While Attending Critical Care Postsimulation Reflective Learning Conversation: A Scoping Review. Issue 2 (March 2023) - Almomani, Emad; Sullivan, Jacqueline; Samuel, Jisha; Maabreh, Ahmed; Pattison, Natalie; Alinier, Guillaume
Abstract : Background: The critical care environment is characterized with a high level of workload, complexity, and risk of committing practice mistakes. To avoid clinical errors, health care professionals should be competent with effective clinical reasoning skills. To develop effective clinical reasoning skills, health care professionals should get the chance to practice and be exposed to different patient experiences. To minimize safety risks to patients and health care professionals, clinical reasoning with a focus on reflective learning conversation opportunities can be practiced in simulated settings. Objectives: To explore the most valid and reliable tools to assess clinical reasoning while attending adult critical care–related simulation-based courses in which reflective learning conversations are used. Methods: A scoping review was conducted following Joanna Briggs Institute and Preferred Reporting Items for Systematic Reviews Extension for Scoping Reviews. Eight electronic databases were searched, and full-text review was completed for 26 articles. Results: The search resulted in no studies conducted to measure clinical reasoning while attending adult critical care–related, simulation-based courses in which the reflective learning conversation method was embedded. Discussion: This highlights the need to evaluate current available clinical reasoning tools or develop new tools within the context of adult critical care simulation where reflective learning forms a key part of the simulation procedures.